Investigation on structure and hydrogen storage performance of as-milled and cast Mg90Al10 alloys. (29th March 2018) - Li, Yaqin; Zhang, Yanghuan; Shang, Hongwei; Qi, Yan; Li, Ping; Zhao, Dongliang
Abstract: The as-milled (20 h) and cast Mg90 Al10 alloys were prepared by mechanical milling and vacuum induction melting, respectively. The differences in the phase composition, apparent morphology and microstructure of the alloys were analyzed by X-ray diffraction (XRD), scanning electron microscope (SEM) and high resolution transmission microscope (HRTEM). The activation performance, hydrogen absorption/desorption rate and pressure-composition-isotherm (P-C-T) curves of the pure Mg, as-milled (20 h) and cast Mg90 Al10 alloys were tested using a Sieverts apparatus. The results show that the alloys both are nanocrystalline structure and consisted of the main phase of Mg phase and the second phase of Al phase or Mg17 Al12 phase. Compared to pure Mg, the thermodynamics and kinetics of the as-milled (20 h) and cast Mg90 Al10 alloys are improved in different degree. The hydrogen desorption enthalpy (Δ H de ) of the as-milled (20 h) and cast Mg90 Al10 alloys are 75.43 and 72.76 kJ mol −1 H2, which are smaller than 100.67 kJ mol −1 H2 of pure Mg. And the dehydrogenation activation energy ( E de (a)) decreases from 172.61 kJ mol −1 H2 of pure Mg to 163.59 and 157.65 kJ mol −1 H2 of the as-milled (20 h) and cast Mg90 Al10 alloys, respectively. However, the activation performance and the hydrogen absorption capacity have the varying degree to drop. Highlights: The as-milled (20 h) and cast Mg90 Al10 alloys are prepared. Hydrogen storage performance and microstructure of the alloys are studied. Thermodynamics and kinetics of the alloys are improved compared to pure Mg. The hydrogen storage mechanisms of the alloys are analyzed.